Pola Penyebaran Varietas Pisang Roid (Musa spp.) Lokal Jatigede di Kecamatan Jatigede Kabupaten Sumedang - Fajar Maulana Wijaya Kusumah; Ade Ismail; Agung Karuniawan; Vika Faradhita Pratiwi; Anjali Detha Safitria (Paspalum: Jurnal Ilmiah Pertanian, 2023)
As time goes by and human efforts to plant and expand new superior species cause local species that are very diverse to be suppressed resulting in decline (inbreeding depression), even genetic drift. one of the local species is banana Roid from Jatigede District. Roid banana is allowed to grow wild without any special care from the local community. The purpose of this study is to identify the potential genetic diversity of local varieties of Roid banana (Musa spp.) in Jatigede District. This research will be conducted in November 2021 – January 2023 in three villages located in Jatigede Sub-district, namely Ciranggem Village, Jemah Village, and Mekarasih Village. The research was conducted using a descriptive method through exploration and characterization that refers to descriptors. Determination of the sample location was done by purposive sampling. Based on the results of the study, Jatigede Sub-district has a wide genetic diversity and distant kinship between Roid banana species. Characters that contribute to inter accession diversity are midrib width (LPt), bunch diameter (DTn), and pseudostem length (PPs). Accession MS1.3 was selected as a superior accession with the characters of the number of combs per bunch, leaf blade width 71-80 cm, leaf blade length 171-220 cm, and the number of rhizomes > 5 tillers..